PERANAN KEPEMIMPINAN DALAM MENINGKATKAN DISIPLIN PEGAWAI PADA BAGIAN UMUM SEKRETARIAT DAERAH KABUPATEN MALINAU - Agustina Randa (ADMINISTRASI PUBLIK, 2019)
Thesis. Departmen Of Administration. Faculty Of Social and Political Scienes. University Of 17 August 1945. Mentor of Drs. Maskan AF. M.Si and mother Dra. Hj. Nanik Pujiastuti, M.Si. The purpose of research is to know to role of leadership in improving the discipline of employees in the General Section of Malinau District Secretariat.Research uses quantitative data. The population in this atudy is the entire employee at the General Section of the Malinau District Secretariat numbering 30 people. Given the number of population in the study sites is relatively small then the number of samples in this study 30 people, data obtained with questionnaire technique, observation, documentation. While the data analysis technique used is the method of Correlation Coefficient correlation Product Moment (Pearson).The results of the analysis have been carried out that there is a significant relationship of leadership role variables with employee discipline variables, because the r-empirical value is greater than the r-theoretical value or 0,473>0,361 at a significant level of 5%.Based on the result of the t-test, it is concluded that there are significant influence and correlation between leadership role variables and employee discipline variable, because the t-emperical value is greater when compared with t-theoretical ie 2,841 > 1,701 at 5% significant level. Suggestions that can be given is the leadership to always improve supervision of employee, in order to prevent the disciplinary action of the employees and for the quality of employment of employees who have been relatively good enough to be maintained and can be upgraded again.